Paradigm Shift in the Eurozone? The Market-Based Convergence Rationale - Simon Tilford; Christian Odendahl (Intereconomics, 2018)
To prevent divergence in a downturn and help cushion economic shocks, capital markets and banks both need to be integrated and assets diversified across Eurozone member states.
Keywords: 330